Theoretical and experimental studies on film boiling of alternative refrigerants - Tan, Hean Seng. (2009)
Experimental and theoretical research on pool boiling heat transfer of nonconventional refrigerants was carried out in this project. The film boiling characteristics of R-22, R-134a. R-123 and R-507 from spheres of diameters 20, 25, 30, 35 and 40 mm were obtained using the quenching technique, and compared with existing correlations. An improved theoretical model was developed numerically based on replacing the set of governing equations in Frederking-Clark's model, which are in Cartesian form, with a set in the spherical co-ordinate system. A new dimensionless term was observed which assisted in the analysis of the model. Empirical equations to fit the experimental data were presented.